An Active Microcurricular Learning Model: A Guide to Classroom Planning for Physical Education - Posso-Pacheco, Richar Jacobo (2020)
This article aimed to describe a microcurricular learning model of Physical Education; the description was based on a bibliographic review of 33 academic texts resulting from the process of inclusion and exclusion criteria. This process was framed in a publication period corresponding to 1994 until 2020, from the Dialnet, Google Scholar databases, and the platform of the Ministry of Education of Ecuador. Four dimensions were analyzed: Ecuadorian Physical Education Curriculum, curricular approaches, active methodologies, and contextualization of content. This analysis contributed to the construction of a curricular proposal that directs students to the development of their motor, social, cognitive, and affective skills, under the mainstreaming of the inclusive, playful, and corporality curricular approaches; it also serves as a planning guide that ensures the autonomy of the students so that they can replicate various physical exercises throughout their lives.